Determinants and impacts of financial literacy in the Lao PDR - Peter J. Morgan; Trinh Q. Long (Asian Development Bank Institute (ADBI), 2019)
Financial literacy is gaining increasing importance as a policy objective in many countries. However, internationally comparable information on financial literacy is still scarce. The Organisation for Economic Cooperation and Development International Network on Financial Education (OECD/INFE) survey of adult financial literacy is a standardized survey instrument, but so far has mainly been implemented in higher-income countries outside of Asia. Our paper extends the literature by conducting the survey in a relatively low-income Asian economy−the Lao PDR−and analyzing the determinants of financial literacy and the effects of financial literacy on other behaviors. We also compare these results with those of our earlier study of financial literacy in Cambodia and Viet Nam. This study of the Lao PDR extends our research in the Cambodia-Lao PDR-Myanmar-Viet Nam (CLMV) region, and the survey was broadened to include more variables that could be used as effective instrumental variables for financial literacy to deal with possible endogeneity problems. This increases our confidence in our findings that financial literacy positively affects both savings and financial inclusion. Generally, our study corroborates the findings of studies of other countries, but uncovers some differences as well. The average financial literacy score in the Lao PDR is found to be 12.5, slightly below that of Viet Nam (12.7) and higher than that of Cambodia (11.8). These scores are at the lower end of the range seen in a sample of 30 economies that have implemented the OECD/INFE survey, but they can be considered normal in view of the low levels of per capita income in these economies. The main determinants of financial literacy are found to be educational level, income, age, and occupational status. Both financial literacy and general education levels are found to be positively and significantly related to savings behavior and financial inclusion, and these results hold even when correcting for possible endogeneity of financial literacy.
Keywords: D14; G11; J26; 330; financial literacy; financial behavior; financial inclusion; household saving; Cambodia; Lao PDR; Viet Nam